MENINGKATKAN KEMAMPUAN MEMASANG KANCING BAJU MELALUI MEDIA MODEL BAGI ANAK TUNADAKSA ( Single Subject Research kelas D/V di SDLB Negeri 64 Surabayo Lubuk Basung) - Andriance - Andriance (Jurnal Penelitian Pendidikan Khusus, 2013)
this research background by a young quadriplegic problem DV class had difficulty in the buttons. From the results of the identification and assessment, children have difficulty in buttoning clothes properly on PMDS subjects. Thus the researcher seeks help to improve the ability to install using the media buttons model. This study aims to improve the ability to install buttons with media usage models for young quadriplegic X. This study receipts experimental approach in the form of Single Subject Research (SSR) with the A-B design and data analysis techniques using visual analysis of analyzes in those conditions. To target the frequency of their behavior when the child is able to put buttons properly given a value of one and if the child is not able to install dress properly given a value of zero The results of this study indicate that based on the analysis of both data analysis and analytical conditions between estimated trend direction, trend stability, trace data and the rate of change increased care overlap positive and less on data analysis. Thus it can be stated thus hypothesis (Ha) is accepted. From the overall results indicate a change in the ability to install X buttons on the child toward better. This means it can be concluded that media models can be used to improve the ability of buttoning clothes for children tunadaksa